The Community Partnership Program Utilization of Cattle Manure as Organic Fertilizer - Hasan, Said; Yusnaini, Yusnaini; Sapsuha, Yusri (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The Community Partnership Program of livestock farmer groups in Doyado Village, East Tidore District, Tidore Islands City, is a community service activity aimed at handling cow manure in Doyado Village, which is currently quite abundant in number but not well managed, so it has the potential to pollute the environment. The purpose of this activity is also to introduce organic fertilizer processing technology and familiarize the use of organic fertilizers to farmer groups in Doyado Village, who have been using cow dung without prior treatment. The methods of implementation include socialization and training, opinion polls through questionnaires, organic fertilizer processing demonstration plots, and focus group discussions. Group discussions were held to discuss the results and equalize perceptions for all participants in the process of making organic fertilizers. Through this activity, cow manure can be used by farmer groups to become organic fertilizer and during this activity can provide organic fertilizer and provide additional income for farmer groups.